I factored it to:

Never equals zero (right?)

How would I solve for ?

Edit: I know the answer is by looking at it, but how would I solve a similar equation?

Printable View

- April 11th 2011, 01:46 PMIanCarneyFinding the roots of this equation

I factored it to:

Never equals zero (right?)

How would I solve for ?

Edit: I know the answer is by looking at it, but how would I solve a similar equation? - April 11th 2011, 01:51 PMPlato
- April 11th 2011, 01:54 PMIanCarney
- April 11th 2011, 01:54 PMTKHunny
Factor in the usual way.

You'll have trouble with the fist piece, for reasons similar to that 3x you already threw out.

You'll need a logarithm or an emperical rule for the last piece. Very informally, ? - April 11th 2011, 02:25 PMe^(i*pi)
- April 11th 2011, 09:10 PMjohnny
y = e^(-3x) - e^(2x) = e^(-3x) (1 - e^(5x)) = 0

1 - e^(5x) = 0

1 = e^(5x)

ln 1 = ln e^(5x) = 5x

ln 1 = 0

∴ x = 0/5 = 0

**Moderator edit:**Quote of OP has been added. This post answers the original question posted. However, it should be noted that in post #3 the original poster gave a new question.